Curriculum design through lesson study. (13th November 2020) - Wake, Geoff; Seleznyov, Sarah
Abstract : page_467 other Lesson study is increasingly prevalent as a collaborative activity in which teachers take part to explore their practice. There are many variations in how lesson study manifests itself, even in Japan, where it originated. However, in Japan, fundamental to lesson study is a focus on collaboration in researching teachers' professional practice. In this article, we draw on experiences of our collaborative research with colleagues in Japan to provide theoretical insights into how we might conceptualize and inform future developments of lesson study as action research that informs curriculum design and implementation. The approach taken develops ideas of the theory of didactical situations, and draws on the construct of boundary objects to understand Japanese lesson study. We identify a class of artefacts, didactical devices, that may provide a useful form of boundary object that supports the collaborative action research of lesson study. Although the particular focus of the work presented here is mathematics, the lessons that we draw should have applicability across the curriculum more widely.